PENGETAHUAN WANITA TENTANG KANKER PAYUDARA - Nur Asiah; Diah Arruum; Ellyta Aizar (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2019)
Introduction about breast cancer is very important in order to decrease new cases through the efforts of prevention and early detection to make it easier to recognize the risk factors and symptoms of breast cancer. This community service activities aiming to identify women's ability to detect early breast cancer. This community service activities performed on May to October 2018 in the UPT PUSKESMAS PB SELAYANG II Medan. The method of implementation of community service activities started by measuring the level of knowledge about society and the cadre of breast cancer, followed by the giving of material (counseling) about breast cancer by SADARI. Results dissemination instruments of knowledge work in the area of women's health centers on breast cancer obtained that 30 women (60%) have less knowledge about breast cancer. For it to do a follow-up to train cadres and taught to the community to recognise and assess the risk factors in a sustainable way next taught how about SADARI techniques and further stages need to be done breast exam by using breasligh.